Cobalt-catalysed unactivated C(sp3)–H amination: two-state reactivity and multi-reference electronic character. Issue 8 (21st March 2019) - Yu, Yang; Luo, Gen; Yang, Jimin; Luo, Yi
Abstract : A remarkable two-state reactivity scenario and an unusual multi-reference character have been computationally found in Co-catalysed C(sp 3 )–H amination. In addition, the investigation on the additive, aminating reagent, metal center, and auxiliary ligand provides implications for development of new catalytic C–H functionalization systems. Abstract : Theoretical calculations have been performed to gain deeper understanding on the mechanism of Cp*Co(iii )-catalysed C(sp 3 )–H amination of 8-methylquinoline with phenyl-1, 4, 2-dioxazol-5-one. The result suggests that the additive AgSbF6 could thermodynamically facilitate the generation of catalytically active species Cp*Co(OPiv) + . The subsequent catalytic cycle involves sequential external base assisted C(sp 3 )–H activation, decarboxylation, nitrene insertion, and protonation. Importantly, a remarkable "two-state reactivity" scenario was disclosed for this reaction. A distinct multi-reference feature was found in the processes for Co-nitrene radical intermediate and C–N bond formations, which thus greatly enriches the cobalt catalysis chemistry. Such a multi-reference character was the outcome of double excitation from the Co–N π-bonding orbital to its antibonding orbital. DFT results indicate that aminating reagents with a rigid structure would be preferred because they form strong orbital interaction with the metal center. In addition, it is theoretically predicted that the Fe(iii ) species is a promising candidate for efficient C(sp 3 )–H activation and Tp (Tp = hydridotris(pyrazolyl)borate) can serve as a more effective ligand for Co(iii ) catalysed C(sp 3 )–H activation, thanks to its stronger interaction with the Co center which thus stabilizes the transition state.